The Relationship of Knowledge and the Initial Actions of the Mother on Toddlers with Diarrhea at Puskesmas Harapan Jayapura Regency - Martina Mogan; Endang Trisnawati (Jurnal EduHealth, 2023)
Diarrhea is a bowel movement with diluted or watery stools three times per day or more, Diarrhea is one of the highest incidence diseases in the world and is reported to have nearly 1.7 billion cases annually. The disease often causes death in children under five years of age (toddlers). The goal is to find out the relationship of maternal knowledge with the initial actions in toddlers with diarrhea. Methods : This study uses descriptive analytics with a cross sectional approach. The research location was at the Harapan Health Center and the time the study was conducted from September to November 2022. The population was 80 toddlers and the study sample was 67 respondents. Sampling was carried out by accidental non random sampling. Data collection techniques use Primary data. Data collection instruments using questionnaires. Data analysis using univariate analysis and bivariate analysis. The results of the study using the chi-square test obtained a value of p = 0.000 for knowledge of maternal knowledge diarrhea in the good category there were 35 people (52.2%) and those who performed the initial action there were 27 people (71.0%) and those who did not take the initial action 8 people (30.0%), the category of knowledge was sufficient there were 27 people (40.3%) and those who performed the initial action there were 11 people (29.0%) and those who did not take the initial action 16 people (59.0%), There were 5 fewer people (7.5%), but none of them did the initial action and also those who did not take the initial action there were 3 people or (11.0%). Conclusion There is an influence between knowledge and the initial action of the mother in toddlers with diarrhea. The better the mother's knowledge, the better the initial action given as an initial treatment of diarrhea in toddlers.